2020
DOI: 10.1155/2020/8965047
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A Mitigates Atherosclerosis by Inhibiting Lipid Accumulation and Inflammatory Response

Abstract: Biochanin A (BCA), a dietary isoflavone extracted from red clover and cabbage, has been shown to antagonize hypertension and myocardial ischemia/reperfusion injury. However, very little is known about its role in atherogenesis. The aim of this study was to observe the effects of BCA on atherosclerosis and explore the underlying mechanisms. Our results showed that administration of BCA promoted reverse cholesterol transport (RCT), improved plasma lipid profile, and decreased serum proinflammatory cytokine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 59 publications
(67 reference statements)
0
20
0
Order By: Relevance
“…In the previous reports, genistein had a hypolipidemic effect on menopausal women with hyperlipidemia [ 43 ] and ameliorated dyslipidemia and hepatic steatosis in hyperlipidemic hmsters [ 32 ] and diabetic mice [ 44 ]. Biochanin A mitigates dyslipidemia in hyperlipidemic mice [ 33 ], atherosclerotic mice [ 45 ], and diabetic rats [ 46 ]. In addition, tectorigenin and prunetin improved the effect of improving dyslipidemia in diabetic rats and obese mice, respectively [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the previous reports, genistein had a hypolipidemic effect on menopausal women with hyperlipidemia [ 43 ] and ameliorated dyslipidemia and hepatic steatosis in hyperlipidemic hmsters [ 32 ] and diabetic mice [ 44 ]. Biochanin A mitigates dyslipidemia in hyperlipidemic mice [ 33 ], atherosclerotic mice [ 45 ], and diabetic rats [ 46 ]. In addition, tectorigenin and prunetin improved the effect of improving dyslipidemia in diabetic rats and obese mice, respectively [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of Dil-ox-LDL by THP-1 macrophage-derived foam cells was performed as previously described [ 9 ]. In brief, THP-1 macrophage-derived foam cells were transfected with LV-Mock or LV-Asprosin for 72 h, washed twice with PBS, and then incubated with 10 μg/mL Dil-ox-LDL for 4 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…ABCA1- and ABCG1-dependent cholesterol efflux is the first and rate-limiting step of reverse cholesterol transport (RCT), a process by which excessive cholesterol in arterial wall cells is delivered by HDL to the liver for further metabolism and excretion [ 5 , 6 ]. Studies from our group and others have demonstrated that astragalin, C1q tumor necrosis factor-related protein 12, fargesin and biochanin A increase RCT efficiency and protect against atherosclerosis in apolipoprotein E-deficient (apoE −/− ) mice by up-regulating ABCA1 and ABCG1 expression [ 7 9 ]. Thus, searching for the novel mechanisms governing expression regulation of these two transporters is of critical importance to develop future therapeutic intervention in atherosclerotic cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…As reflected by the results of CCK-8 and scratch test (Figure 1E,1F, Figure S1A), ox-LDL strikingly enhanced cell viability and migration in VSMCs, whilst treatment with genistein markedly reduced the viability and migration of ox-LDL-exposed VSMCs. Uptake of large amounts of fat by VSMCs leads to cholesterol accumulation, which foams the cells, causing AS (20). Oil Red O staining (Figure 1G) demonstrated a dramatic increase of intracellular lipid particles in ox-LDL-exposed VSMCs and noticeable decline of intracellular lipid particles inox-LDL-exposed VSMCs following genistein treatment.…”
Section: Genistein Alleviated As In Rats and Inhibited Ox-ldlinduced ...mentioning
confidence: 99%